Differential regulation of glucolipid metabolism by acute hypoxia in gibel carp (Carassius gibelio) strains - Liyun Wu; Chaoyue Li; Qiaozhen Chen; Yu Wang; Rui Zhang; Haokun Liu; Dong Han; Zhimin Zhang; Xiaoming Zhu; Yunxia Yang; Shouqi Xie; Junyan Jin (Aquaculture Reports, 2024)
This study investigated the responses of glucolipid metabolism in gibel carp, the CAS III strain (A strain, 7.14 ± 0.23 g) and the Dongting strain (DT strain, 7.72 ± 0.54 g), following acute hypoxia/reoxygenation. The effects of hypoxia (0.39 ± 0.02 mg/L) and reoxygenation (8.30 ± 0.30 mg/L) were examined in both strains after exposure for 2 h. The results revealed significantly enhanced PI3K/AKT pathway and AMPK/HIF-1α pathways, along with upregulated expression of glucose-6-phosphatase (g6pase) and lipid synthesis-related genes (acc and fas) in both gibel carp strains following acute hypoxia (P < 0.05). The observed increase in plasma glucose levels during acute hypoxia may be related to elevated expression of g6pase (P < 0.05). Regarding the genotype, the A strain exhibited significantly higher expression of glucose metabolism-related genes (pk and pepck) in the liver compared to the DT strain (P < 0.05). Conversely, the expression of lipid metabolism-related genes (hsl, lpl, pparα, cpt1a, and aco3) were significantly lower in the A strain compared to the DT strain (P < 0.05). In both strains of gibel carp, reoxygenation resulted in significant activation of the PI3K/AKT and AMPK/mTOR pathways, accompanied by upregulated expression of glucose metabolism-related genes (gk, 6pfk, foxo1a, fbpase, and pepck) and lipid synthesis-related genes (srebp-1, acly, and acc) (P < 0.05). Notably, the A strain exhibited increased transcripts of glucose metabolism-related genes (gk, pk, foxo1a, g6pase, and pepck) and lipid metabolism-related genes (acly, fas, and cpt1a) compared to the DT strain (P < 0.05). Overall, this study revealed distinct regulation patterns of glucolipid metabolism in the gibel carp with different genotype under acute hypoxia/reoxygenation.